2015
DOI: 10.1161/hypertensionaha.115.05948
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Intake

Abstract: High salt intake is the major cause of raised blood pressure and accordingly leads to cardiovascular diseases. Recently, it has been shown that high salt intake is associated with an increased risk of obesity through sugar-sweetened beverage consumption. Increasing evidence also suggests a direct link. Our study aimed to determine whether there was a direct association between salt intake and obesity independent of energy intake. We analyzed the data from the rolling cross-sectional study–the UK National Diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
136
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(149 citation statements)
references
References 31 publications
11
136
1
1
Order By: Relevance
“…Most of the study participants were either overweight (41%) or obese (25%). Recent observational studies have explored the relationship between sodium intake measured in 24-hour urine collection samples and obesity, BMI, weight, and waist circumference, with similar results to the present study (Figure 2) [22,23]. The positive correlation between increased body size parameters and higher salt consumption is considered an independent risk factor of obesity.…”
Section: Discussionsupporting
confidence: 86%
“…Most of the study participants were either overweight (41%) or obese (25%). Recent observational studies have explored the relationship between sodium intake measured in 24-hour urine collection samples and obesity, BMI, weight, and waist circumference, with similar results to the present study (Figure 2) [22,23]. The positive correlation between increased body size parameters and higher salt consumption is considered an independent risk factor of obesity.…”
Section: Discussionsupporting
confidence: 86%
“…However, we have found that high salt diets can also induce hepatic aldose reductase expression (due to effects on osmolarity) leading to endogenous fructose production and NAFLD in mice, and mice lacking fructokinase are protected (Lanaspa MA, manuscript under review). High salt diets are independently associated with metabolic syndrome/diabetes (135, 136) and NAFLD (137). Thus, it seems likely that both high glycemic diets and/or high salt diets might exacerbate fructose-induced NAFLD.…”
Section: Modulating Factorsmentioning
confidence: 99%
“…study 42 that proves that eating salt increased the chance of obesity, independent of energy intake. Several mechanisms have been proposed for this association, including increased water consumption, a consequent increase in the volume of extracellular water, and changes in fat metabolism following salt intake.…”
Section: Discussionmentioning
confidence: 81%